Among the various lives of cats and the many identities of chameleons:: the traditional communities of the Cerrado - Minas Gerais State/Brazil (Élisée - Revista de Geografia da UEG, 2020)
This text presents elements on the historical trajectory of occupation of the Cerrado, reflecting on how this process has contributed to the formation of traditional communities in the territories that make up this biome. We understand that the way of life of these communities has been threatened by a series of transformations that have occurred throughout the 20th century, and these threats also impact the communities and contribute to their organization and to the development of collective alternatives for social and cultural resistance.Keywords: Traditional communities. Thick. Environmental History.